Karakteristik Pencernaan Makanan Fermentasi oleh Bakteri Asam Laktat dan Manfaatnya Bagi Kesehatan - Wijaya, Putu Austin Widyasari; Pharmawati, Made; Gde Evayanti, Luh (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 2 (2024): Jurnal ITEPA, 2024)
Nowadays fermented foods are increasingly consumed by the public. Fermentation is a food processing process by breaking down organic compounds carried out by microorganisms, especially lactic acid bacteria (LAB). Various types of LAB-fermented foods comes both from local and foreign countries such as kefir; dairy product such as yogurt, and cheese; plant-based food such as sauerkraut, kimchi, pickles, fermented cassava, and tempe. This type of food is believed to have various health benefits such as improving digestive health through maintaining control of pathogenic intestinal microflora, helping the absorption of certain nutrients, and improving the immune system. Previous studies have shown that fermented foods affect the absorption of protein and minerals (iron, zinc). Some study has shown that exopolysaccharides (EPS) from LAB has an antioxidant effect. Therefore, this review study aims to determine the absorption characteristics of nutrients from LAB fermented foods and how they affect digestive health.